Surpassing wantonness by appealing to emotions :|a Neo-Frankfurtian approach to freedom of the will - Boylu, Ayça. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2004., 2004)
In this thesis, I question whether certain kinds of emotions are necessary for one's realization of freedom. In searching an answer to this question, I focus on a specific approach to freedom, namely the Frankfurtian approach. I modify this approach and construct a Neo-Frankfurtian approach. First I single out the second order volitions necessary for one's realization of freedom because of an objection Harman makes. I call these necessary second-order volitions 'creative effective second-order volitions'. I also defend the position that one realizes freedom only if she takes steps in accordance with who she desires to become. I refer to that imaginary person by the term 'desired-self'. Critically exposing Watson's objection, I argue that the value judgment "my becoming my desired self is valuable" must underlie the formation of creative effective second-order volitions. Finally I detect a motivational problem. Even if one makes this value judgment, I argue that one may remain unmotivated in taking steps towards one's desired-self. Hence I conclude that certain kinds of emotions must generate this value judgment and constitute the motivation that is necessary for one's realization of freedom of volition. My suggestion as one of these emotions is a certain kind of discontentment that stems from realizing the gap between who one believes she is and her desired-self.
Keywords: Free will and determinism.; Emotions (Philosophy)